Analisis Hubungan Komunikasi dan Lingkungan Kerja Terhadap Keterlibatan Kerja Melalui Kepuasan Kerja Sebagai Variabel Mediasi pada AirNav Indonesia Cabang Semarang - Rizka Alfira Fitriana; Masitha Fahmi wardhani; Sih Darmi Astuti; Artha Febriana (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study aims to analyze the relationship between communication and work environment on work engagement with job satisfaction as a mediating variable at AirNav Indonesia Semarang Branch. This study was motivated by the low level of employee work engagement. The approach used was quantitative with the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method. The study population was all 62 employees of AirNav Indonesia Semarang Branch, so a saturated sampling technique was used. Data were collected through a Likert-scale 5 questionnaire. The results showed that communication and work environment had a significant effect on job satisfaction and work engagement, and job satisfaction acted as a mediating variable in the relationship between communication and work environment on work engagement.